Partial Anomalous Pulmonary Venous Return Diagnosed by Central Catheter Misplacement - Reichert, Lena; Bougioukas, Ioannis; Seipelt, Ralf; Huwer, Hanno (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Anomalous venous connections of the left lung can either affect all of the veins or only the upper lobe. They mostly drain into the innominate vein. We present the case of a patient who underwent a coronary bypass operation and was prepared with insertion of central lines including Swan-Ganz catheter through both the internal jugular veins. Blood gas analysis obtained from these catheters suggested the presence of a left-to-right shunt. CT (computed tomography) imaging confirmed a pulmonary venous anomaly with misplacement of the left-sided catheter in an abnormal pulmonary vein. Such a rare condition can be suspected by obtaining arterialized blood samples and measuring the mean pressure through central catheters.
Keywords: pulmonary veins; surgery; cardiac anatomy